Tindak Pidana Kekerasan di Desa Duduk Sampeyan dalam Perspektif Hukum Pidana Islam - Budi Sutomo (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2019)
The criminal acts that often happen in people's lives are related to a violent crime, one of which occurred in Duduk Sampean Gresik, which has the court decision. This paper aims to analyze the decision of the Gresik district court regarding the violent crime that occurred in Duduk Sampean. This paper concludes three things in this research, namely: (1) the three individuals are Muslims and they are mukallaf who are responsible for their jari>mah (Illegal act or ommission), their action is classified as jari>mah tawa>fuq so that each one is only responsible for their owns actions; (2) the imprisonment imposed by the Gresik District Court is classified as a ta'zi>r sentence which falls under the authority of ulil amri or the government even though it has been freed from the qisa>s punishment and diyah for getting forgiveness; and (3) the restitution received by the victim constitutes the realization of the legal liability of the offender for obtaining forgiveness.